Review of Silicon Photonics Technology and Platform Development - Siew, S. Y.; Li, B.; Gao, F.; Zheng, H. Y.; Zhang, W.; Guo, P.; Xie, S. W.; Song, A.; Dong, B.; Luo, L. W.; Li, C.; Luo, X.; et al. (Journal of lightwave technology, 2021)
Many breakthroughs in the laboratories often do not bridge the gap between research and commercialization. However, silicon photonics bucked the trend, with industry observers estimating the commercial market to close in on a billion dollars in 2020 [45] . Silicon photonics leverages the billions of dollars and decades of research poured into silicon semiconductor device processing to enable high yield, robust processing, and most of all, low cost. Silicon is also a good optical material, with transparency in the commercially important infrared wavelength bands, and is a suitable platform for large-scale photonic integrated circuits. Silicon photonics is therefore slated to address the world's ever-increasing needs for bandwidth. It is part of an emerging ecosystem which includes designers, foundries, and integrators. In this paper, we review most of the foundries that presently enable silicon photonics integrated circuits fabrication. Some of these are pilot lines of major research institutes, and others are fully commercial pure-play foundries. Since silicon photonics has been commercially active for some years, foundries have released process design kits (PDK) that contain a standard device library. These libraries represent optimized and well-tested photonic elements, whose performance reflects the stability and maturity of the integration platforms. We will document the early works in silicon photonics, as well as its commercial status. We will provide a comprehensive review of the development of silicon photonics and the foundry services which enable the productization, including various efforts to develop and release PDK devices. In this context, we will report the long-standing efforts and contributions that previously IME/A * STAR and now AMF has dedicated to accelerating this journey.